2016
DOI: 10.1177/0047287516667848
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tourism on Economic Growth and CO2 Emissions: A Comparison between Developed and Developing Economies

Abstract: The objective of this study is to empirically examine the effect of tourism on economic growth and CO2 emissions across the panels of developed and developing economies around the world.The study also investigates the Environmental Kuznets Curve (EKC) hypothesis between tourism revenue and CO2 emissions. To achieve these objectives, study employs robust panel econometric techniques on balanced panel data sets of developed and developing economies.The cointegration test results confirm the long-run equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
208
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 409 publications
(228 citation statements)
references
References 65 publications
(97 reference statements)
18
208
0
2
Order By: Relevance
“…For instance, our results establish tourism-led growth hypothesis, i.e., the income level of a country's tourist arrivals positively contributes to economic growth. Our results confirm the tourism-led-growth hypothesis and are also consistent with the previous empirical studies [5,23], which document that the tourism has a significant positive impact on economic growth. Therefore, to ensure a solid growth performance, the policymakers in these countries can implement some policies to upgrade the income level of a country's tourist arrivals.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, our results establish tourism-led growth hypothesis, i.e., the income level of a country's tourist arrivals positively contributes to economic growth. Our results confirm the tourism-led-growth hypothesis and are also consistent with the previous empirical studies [5,23], which document that the tourism has a significant positive impact on economic growth. Therefore, to ensure a solid growth performance, the policymakers in these countries can implement some policies to upgrade the income level of a country's tourist arrivals.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
“…The authors have concluded that tourism has a positive and important contribution to economic growth for the country group, including China, France, Germany, Italy, Mexico, Russia, Spain, Turkey, the United Kingdom, and the United States. Another recent study, by [23], has confirmed that tourism has a considerable positive impact on economic growth across the panels of developed and developing economies around the world. Several previous studies [24,25] also highlight the issue of overtourism, though our focus in this paper is to empirically examine the impact of tourism quality on economic development and environment.…”
Section: Tourism and Economic Growth Nexusmentioning
confidence: 91%
“…Katircioglu [10] applied a trivariate framework and found that tourism development in Turkey contributes to high energy consumption and carbon dioxide emanations. Paramati, Alam [52] found that tourism impact on carbon dioxide emanations is faster in developing than advanced economies. Although a considerable number of studies suggest that tourism contributes to CO 2 emissions, yet few studies also suggest the opposite, i.e., CO 2 emissions decrease tourist arrivals [53].…”
Section: Relationship Between Tourism and Carbon (Co 2 ) Emissionsmentioning
confidence: 99%
“…Tourism stimulates air environmental changes in a positive way and also is affected by such changes [29]. For instance, 1% of increase in tourism revenue contributes to the 0.105% reduction of CO 2 emissions [30], and the developing countries have slower reduction speeds than the developed countries [31]. Furthermore, being considered as the low-carbon industry [32], tourism activities contribute to the upgrade of industrial structures and the renewal of urban functions, which helps better air environment protection [33,34].…”
Section: E Effects Of Tourism On Air Environmentmentioning
confidence: 99%